The ethics of war essays - Bazargan, Saba; Rickless, Samuel Charles 1964- (Oxford University Press, 2017)
Some of the most basic assumptions of Just War theory have been dismantled in a barrage of criticism and analysis in the first dozen years of the twenty-first century. 'The Ethics of War' continues and pushes past this trend. This anthology is an authoritative treatment of the ethics and law of war by eminent scholars who first challenged the orthodoxy of Just War theory, as well as by 'second-wave' revisionists